Regulation and Wage Bargaining - D.M. Dalen; N.-H. M. von der Fehr; E. R. Moen (University of Oslo, Department of Economics, 1998)
In many regulated industries labour uions are strong and there is clear empirical evidence of labour rent-sharing. We study optimal regulation in a model in which wages are determined endogenously by wage bargaining at the firm level. Compared to the case in which wages do not depend on the regime under which the firm is regulated, allowing for endogenously determined wages has ambiguous effects on the regulatory contract.
Keywords: J3; L51; 330; wages; bargaining; regulation